Oxidative stress-mediated antibacterial activity of graphene oxide and reduced graphene oxide in Pseudomonas aeruginosa - Gurunathan S (Dove Medical Press, 2012)
Sangiliyandi Gurunathan, Jae Woong Han, Ahmed Abdal Dayem, Vasuki Eppakayala, Jin-Hoi KimDepartment of Animal Biotechnology, Konkuk University, Seoul, South KoreaBackground: Graphene holds great promise for potential use in next-generation electronic and photonic devices due to its unique high carrier mobility, good optical transparency, large surface area, and biocompatibility. The aim of this study was to investigate the antibacterial effects of graphene oxide (GO) and reduced graphene oxide (rGO) in Pseudomonas aeruginosa. In this work, we used a novel reducing agent, betamercaptoethanol (BME), for synthesis of graphene to avoid the use of toxic materials. To uncover the impacts of GO and rGO on human health, the antibacterial activity of two types of graphene-based material toward a bacterial model P. aeruginosa was studied and compared.Methods: The synthesized GO and rGO was characterized by ultraviolet-visible absorption spectroscopy, particle-size analyzer, X-ray diffraction, scanning electron microscopy and Raman spectroscopy. Further, to explain the antimicrobial activity of graphene oxide and reduced graphene oxide, we employed various assays, such as cell growth, cell viability, reactive oxygen species generation, and DNA fragmentation.Results: Ultraviolet-visible spectra of the samples confirmed the transition of GO into graphene. Dynamic light-scattering analyses showed the average size among the two types of graphene materials. X-ray diffraction data validated the structure of graphene sheets, and high-resolution scanning electron microscopy was employed to investigate the morphologies of prepared graphene. Raman spectroscopy data indicated the removal of oxygen-containing functional groups from the surface of GO and the formation of graphene. The exposure of cells to GO and rGO induced the production of superoxide radical anion and loss of cell viability. Results suggest that the antibacterial activities are contributed to by loss of cell viability, induced oxidative stress, and DNA fragmentation.Conclusion: The antibacterial activities of GO and rGO against P. aeruginosa were compared. The loss of P. aeruginosa viability increased in a dose- and time-dependent manner. Exposure to GO and rGO induced significant production of superoxide radical anion compared to control. GO and rGO showed dose-dependent antibacterial activity against P. aeruginosa cells through the generation of reactive oxygen species, leading to cell death, which was further confirmed through resulting nuclear fragmentation. The data presented here are novel in that they prove that GO and rGO are effective bactericidal agents against P. aeruginosa, which would be used as a future antibacterial agent.Keywords: graphene oxide, reduced graphene oxide, beta-mercaptoethanol, oxidative stress, antimicrobial activity